2011
DOI: 10.1016/j.canlet.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Neo-angiogenesis and the premalignant micro-circulatory augmentation of early colon carcinogenesis

Abstract: Spectroscopic techniques have demonstrated that in the microscopically normal mucosa, there is an increase in mucosal micro-circulation in patients harboring neoplasia elsewhere in the colon (i.e. marker of field carcinogenesis). However, the physiological and molecular basis of this early increase in blood supply (EIBS) has not been elucidated. We, therefore, investigated the microvessel density (MVD) and angiogenic gene expression in the premalignant colonic mucosa from the well-validated azoxymethane (AOM)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
1
26
0
3
Order By: Relevance
“…Previous studies showed that the micro vessel density occurs in the early colon carcinogenesis and was accentuated at the bottom of crypt 46 . MVD is a well-established technique to assess angiogenesis in colon cancer and has prognostic significance 47 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies showed that the micro vessel density occurs in the early colon carcinogenesis and was accentuated at the bottom of crypt 46 . MVD is a well-established technique to assess angiogenesis in colon cancer and has prognostic significance 47 .…”
Section: Discussionmentioning
confidence: 96%
“…MVD is a well-established technique to assess angiogenesis in colon cancer and has prognostic significance 47 . Neo-angiogenesis have potential implications as a target for chemoprevention 25, 46 .…”
Section: Discussionmentioning
confidence: 99%
“…To quantify this result, we tested the hypothesis that the average hemoglobin concentration measured with a pressure <112 mN∕mm 2 was greater than the average hemoglobin concentration measured with a pressure >112 mN∕mm 2 . A T-test shows that the hypothosis is correct (α ¼ 0.01).…”
Section: Effects Of Force On Measured Hemoglobin Concentrationmentioning
confidence: 99%
“…1 Vascular changes occur quite early in the disease progression leading to colon cancer based on a study of a well-established model system. 2 In oral tissue, microvessel density is reported to increase as pathology changes from normal to dysplastic to squamous cell carcinoma. 3,4 For breast cancer, some studies have demonstrated a correlation between angiogenesis (microvessel density) and clinicopathologic parameters, although there are discrepancies in results, some of which likely arise as a consequence of the variety of techniques (e.g., immunohistochemistry and visual microscopy) used to assess angiogenesis and microvessel density.…”
Section: Introductionmentioning
confidence: 99%
“…Our optical and histological investigations in human patients and animal models of colon carcinogenesis have shown diagnostic alterations in hemoglobin concentration that are present in the mucosa but attenuated at deeper submucosal depths. [1][2][3][4][5] Studies with angle-resolved low-coherence interferometry demonstrate that elevation of nuclear diameter associated with dysplasia in Barrett's esophagus was only detectable at a depth of 200 to 300 μm and not observable at 0 to 100 μm or 100 to 200 μm. 6 Several fiber-optic probe modalities have been developed to target the mucosal layer with a wide field of view.…”
Section: Introductionmentioning
confidence: 99%